2021
DOI: 10.1093/g3journal/jkab370
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of BSA-seq experiment for QTL mapping

Abstract: Deep sequencing-based bulked segregant analysis (BSA-seq) has become a popular approach for quantitative trait loci (QTL) mapping in recent years. Effective statistical methods for BSA-seq have been developed, but how to design a suitable experiment for BSA-seq remains unclear. In this paper, we show in theory how the major experimental factors (including population size, pool proportion, pool balance, and generation) and the intrinsic factors of a QTL (including heritability and degree of dominance) affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The high population size coupled with a wholegenome sequencing approach at high coverage was able to optimize most of the factors on which the success of BSA studies rely, (de la Fuente Cant ó & Vigouroux, 2022; Huang et al, 2022;Magwene et al, 2011). In BSA studies that have been performed so far, the sizes of the investigated populations were generally small, often around 200 individuals, though they can range from <100 to >10 000 individuals (reviewed in Huang et al, 2022). Pool sizes were also variable, ranging from only five individuals per pool to more than 400.…”
Section: Discussionmentioning
confidence: 99%
“…The high population size coupled with a wholegenome sequencing approach at high coverage was able to optimize most of the factors on which the success of BSA studies rely, (de la Fuente Cant ó & Vigouroux, 2022; Huang et al, 2022;Magwene et al, 2011). In BSA studies that have been performed so far, the sizes of the investigated populations were generally small, often around 200 individuals, though they can range from <100 to >10 000 individuals (reviewed in Huang et al, 2022). Pool sizes were also variable, ranging from only five individuals per pool to more than 400.…”
Section: Discussionmentioning
confidence: 99%
“…The high population size coupled with a whole-genome sequencing approach at high coverage was able to optimize most of the factors on which the success of BSA studies rely, (Magwene et al, 2011;de la Fuente Cantó and Vigouroux, 2022;Huang et al, 2022). In BSA studies that have been performed so far, the sizes of the investigated populations were generally small, often around 200 individuals, though they can range from <100 to >10,000 individuals (reviewed in Huang et al, 2022). Pool sizes were also variable, ranging from only five individuals per pool to more than 400.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the various mapping studies reported the bulk sizes in the range of 3–11.9% (Takagi et al, 2013 ; Singh et al, 2016 ; Wei et al, 2016 ; Ramos et al, 2020 ). The filial populations produced through selfing can significantly increase the power and precision, especially from F 2 to F 3 , and have been used in the present study (Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%